An in vitro model of drug-resistant seizures for selecting clinically effective antiseizure medications in Febrile Infection-Related Epilepsy Syndrome - Cerovic, Milica; Di Nunzio, Martina; Craparotta, Ilaria; Vezzani, Annamaria (Frontiers in Neurology, 2023)
FIRES is a rare catastrophic epileptic encephalopathy induced by acute unremitting seizures that occur suddenly in healthy children or young adults after a febrile illness during the preceding two weeks. This condition results in high mortality, neurological disability, and drug-resistant epilepsy. The development of new therapeutics is urgently needed and it would be greatly facilitated by validated experimental models, which are still missing. Here, we present the refinement of an in vitro model of mouse hippocampal/temporal cortex acute slices where drug-resistant epileptic activity is induced by zero Mg2+ and 100 µM 4-aminopirydine. Since clinical evidence suggests that acute unremitting seizures in FIRES are promoted by a pathological neuroinflammatory state triggered in the brain by the preceding infection, we mimicked this inflammatory component by exposing slices for 30 min to 10 µg/ml lipopolysaccharide (LPS). LPS induced a sustained neuroinflammatory response, as shown by increased hippocampal mRNA levels of IL-1, CXCL1 (IL-8) and TNF, and increased IL-1/IL-1Ra ratio, and it exacerbated the epileptiform activity in slices, as assessed by multielectrode array recordings. Notably, the epileptiform discharges developing in the presence of neuroinflammation were refractory to maximal therapeutic concentrations of antiseizure medications (ASMs) such as phenytoin (50 µM), sodium valproate (800 µM), and phenobarbital (100 µM), similar to the clinical condition. Treatment of LPS-exposed slices with two medically used immunomodulatory drugs, a mouse anti-IL-6 receptor antibody (100 µM) corresponding to tocilizumab in humans, or anakinra (1.3 µM) which blocks the IL-1 receptor type 1, delayed the onset of the epileptiform events and strongly reduced the ASM-resistant epileptiform activity evoked by neuroinflammation. These drugs were recently shown to reduce drug-refractory seizures in FIRES patients. The neuroinflammatory component and the pharmacological responsiveness of epileptiform events provide a proof-of-concept validation of this in vitro model for the rapid selection of new treatments apt to rapidly terminate acute ASM-refractory seizures in FIRES.